Wave Transformation Pattern in Submerged Breakwater Planning with 2D Wave Model at Mengening Beach, Badung Regency, Bali, Indonesia - Damayanthi, I Dewa Ayu Meia; Eryani, I Gusti Agung Putu; Bagiarta, I Ketut Yasa (Fakultas Teknik Universitas Brawijaya, 2023)
Mengening Beach is located in Badung Regency, Bali, Indonesia. The average erosion rate in Badung Regency is 1.96 m/year, so the right plan is a submerged breakwater to reduce wave energy coming to the beach, which causes erosion. This building artistically does not lessen the beauty of the beach and sea because it’s below the sea mean sea water level (MSL). Because the beach is a tourist area, it is essential to maintain the beauty of the beach. Two-dimensional wave modeling uses the CMS Wave model on SMS software version 10.1 with two modeling scenarios: before and after there is a submerged breakwater. The two-dimensional wave results show that the submerged breakwater plan can dampen waves in the building placement area, which was initially 1.3 m-1.4 m high to 0.9 m-1.3 m, so this submerged breakwater plan can reduce waves by 10%-40%. From this research, readers can learn how to plan a submerged breakwater and know the performance of the planned breakwater function at Mengening Beach.